Comparative-Study of Agrobacterium Biotypes 1, 2 and 3 by Electrophoresis and Serological Methods - Alarcon, B.; López, María M.; Cambra, Mariano; Ortiz Marcide, Jesús M. (2017)
A comparative study by electrophoresis and serology of strains representing the three Agrobacterium biotypes was carried out. Thirteen Spanish isolates and strains from international collections were included. Ten antisera were prepared by using strains from the three biotypes and different types of antigens. The strains were studied by immunodiffusion, indirect immunofluorescence and indirect ELISA. Serological relationship among all the strains was observed, although serological heterogeneity within each of the biotypes occurred. Biotype 3 appears as serologically related to biotypes 1 and 2, having an intermediate position. This observation is in agreement with their biochemical characteristics. Electrophoretic analysis of the three biotypes showed that there was high variability. Three main bands appeared in the six strains studied. One specific band occurred in the biotype 1 strains and another in the biotype 3 strains.